Penerapan Model Pembelajaran Konstruktivisme Menggunakan Media Google Classroom untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Dasar-Dasar Desain Komunikasi Visual Kelas X di SMKN 3 Kuningan - Yusanto, Aorta Prakabayu; Ripai, Ipan (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the learning outcomes of students using the constructivism method using google classroom media in the subject of Visual Communication Design Basics class X SMKN 3 Kuningan in 2023/2024. The method used was quantitative with the type of quasi-experimental method with a pretest-posttest control group design. The population in this study is class X students of SMKN 3 Kuningan. The sample used in this study was divided into 2 classes (experimental and control) with a total of 72 students. The data collection techniques used in this study are tests and questionnaires. The data analysis techniques used in this study are using normality tests, homogeneity tests, hypothesis tests, validity tests, and reliability tests. The results of this study show that the learning outcomes of students in the subject of Fundamentals of Visual Communication Design of CorelDraw material in class X at SMKN 3 Kuningan before using the Constructivism learning model are still lacking with an average score of 77.78. Student learning outcomes in the subject of Fundamentals of Visual Communication Design CorelDraw material in class X at SMKN 3 Kuningan after using the Constructivism learning model are good with an average score of 84.72. There was a change in the learning model of Constructivism on student learning outcomes in the basic subjects of visual communication design